DebrisWatch I: A survey of faint geosynchronous debris. Issue 1 (1st January 2021) - Blake, James A.; Chote, Paul; Pollacco, Don; Feline, William; Privett, Grant; Ash, Andrew; Eves, Stuart; Greenwood, Arthur; Harwood, Nick; Marsh, Thomas R.; Veras, Dimitri; Watson, Christopher
Highlights: A survey of the geosynchronous region was conducted with the Isaac Newton Telescope, La Palma. A population of faint, uncatalogued debris was uncovered in the vicinity of the geosynchronous Protected Region. Many faint, uncatalogued detections show optical signatures of rapid tumbling. Abstract: Recent anomalies exhibited by satellites and rocket bodies have highlighted that a population of faint debris exists at geosynchronous (GEO) altitudes, where there are no natural removal mechanisms. Despite previous optical surveys probing to around 10–20 cm in size, regular monitoring of faint sources at GEO is challenging, thus our knowledge remains sparse. It is essential that we continue to explore the faint debris population using large telescopes to better understand the risk posed to active GEO satellites. To this end, we present photometric results from a survey of the GEO region carried out with the 2.54 m Isaac Newton Telescope in La Palma, Canary Islands. We probe to 21st visual magnitude (around 10 cm, assuming Lambertian spheres with an albedo of 0.1), uncovering 129 orbital tracks with GEO-like motion across the eight nights of dark-grey time comprising the survey. The faint end of our brightness distribution continues to rise until the sensitivity limit of the sensor is reached, suggesting that the modal brightness could be even fainter. We uncover a number of faint, uncatalogued objects that show photometric signatures of rapid tumbling, many of which straddle the limiting magnitude of our survey over the course of a single exposure, posing a complex issue when estimating object size. This work presents the first instalment of DebrisWatch, an ongoing collaboration between the University of Warwick and the Defence Science and Technology Laboratory (UK) investigating the faint population of GEO debris.